Self-efficacy among nursing assistants in Denmark after dementia specific education. (30th September 2020) - Rasmussen, B M; Waldorff, F B; Berg-Beckhoff, G; Andersen, P T
Abstract: Background: The care needs for people with dementia (PWD) constantly needs adjustment which makes it difficult for nursing assistants (NA) to accommodate optimal care to PWD. Dementia education to NAs may increase staff skills, self-efficacy and care quality. The study aims to investigate NA's experience of self-efficacy and how it changes during dementia education. Methods: NAs received dementia-specific education focusing on behavior management through a person-centered approach. A phenomenological hermeneutic study using semi-structured interviews with 18 NA from two municipalities in Southern Denmark. Interviews lasted approx. one hour and were conducted at worksites. Analyses were made with a phenomenological hermeneutic approach. Concept maps were constructed during the process to follow changes in understanding. Results: Dementia education increases the feeling of self-efficacy for NAs through acknowledgement, trial-and-error and social inspiration by peers and educators. NAs experience dementia education differently depending on whether NAs have a structural or citizen-centered focus to their work. NAs with a citizen-centered focus experience greater impact and that higher self-efficacy increases motivation for action and providing good care. They also more frequently experience successful situations due to a more analytic approach to daily challenges. NAs with structural-centered focus identified several structural barriers to establish new routines and therefore did not experience the same increase in self-efficacy. Conclusions: Higher feeling of self-efficacy among NAs after dementia education seems to produce more motivation and engagement in daily care. NAs with a citizen-centered focus in their work, experience a higher level of self-efficacy and are frequently confirmed in this belief. Key messages: Increasing needs for continuing dementia education. Nursing assistants with citizen-centered focus experience greater impact of dementia education.